(3GdQjGOI(B- (3GdJWHjbs - (3TQja eGgQ(B, (3gjcds ([(3O(B.(3e(B]:s (3ecJHI GdMQjI ddfTQ h GdJhRjY(B,s, 2007)
(3jVe GdedGeM GdCSGSjI ddJLGQI GdHjFjI GdYQHjI, GdJMOjGJ GdJj JhGLg GdJLGQI GdHjFjI GdYQHjI aj EWGQ GdfXGe GdYGdej GdLOjO, eaghe hfWGb Gdfbd HGdSjGQGJ Hjf GdOhd GdYQHjI, GSJQGJjLjI JNWjW Gdfbd HGdSjGQGJ, GdOhQ GdeQJbH ddfbd HGdSjGQGJ dOYe GdJLGQI GdHjFjI GdYQHjI, GdfJGFL hGdJhUjGJs
(3HjHdjhZQGajG(B: (3U U(B.156-160s
Keywords: (3GdJLGQIs; (3Gdfbd(B- (3GdLhGfH GdHjFjIs